2010
DOI: 10.4028/www.scientific.net/amr.146-147.1638
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Laser Melting Deposited TiAl Intermetallic Alloy on Titanium Alloy

Abstract: To improve the wear resistance of Titanium alloy, TiAl intermetallic claddings were fabricated on TC4 substrate using laser melting deposition technology. Optical microscope, scan electron microscope (SEM), energy dispersive spectrometer (EDS) and X-ray diffraction meter were applied to investigate the deposited TiAl layer and their interface with substrate. Using hardness tester and M-2000 wear testing machine, hardness, frictional coefficient and wear resistance of the TiAl layers and TC4 alloy were tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Однако ввиду своей высокой хрупкости, особенно фазы TiAl 3 , их применение в качестве объемных материалов не рационально. Работы [26][27][28] были посвящены получению и изучению покрытий и поверхностных слоев на основе данных интерметаллидов. Результаты исследований показали повышение как прочностных характеристик до 20 %, так и износостойкости на несколько порядков при толщине покрытия менее 16 мкм.…”
Section: введение введениеunclassified
“…Однако ввиду своей высокой хрупкости, особенно фазы TiAl 3 , их применение в качестве объемных материалов не рационально. Работы [26][27][28] были посвящены получению и изучению покрытий и поверхностных слоев на основе данных интерметаллидов. Результаты исследований показали повышение как прочностных характеристик до 20 %, так и износостойкости на несколько порядков при толщине покрытия менее 16 мкм.…”
Section: введение введениеunclassified
“…For the intermetallic compounds, γ-TiAl is a promising one due to the combination of high hardness, oxidation resistance, and satisfactory plasticity relative to the non-equiatomic phases [29]. Zhang et al [30] showed that a γ-TiAl coating deposited on a TC4 titanium alloy had high wear resistance in dry friction against a steel ball.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the mentioned above research papers were focused on the development of the methods of the surface modification of the titanium alloys, or the approaches to form desirable intermetallic phases in Ti-Al system. For the initial characterization of the microstructure, metallography, scanning electron microscopy, and X-ray diffraction methods have been successfully used [7][8][9][10]13,17,30,31,33,35,36,42,51]. However, detailed study of the microstructure in gradient materials requires the application of analytical methods with high resolution, such as transmission electron microscopy, which was successfully used previously [14,22,32,34,42,46,54,58].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their low density, high specific strength, and good creep resistance, TiAl alloys are new lightweight high-temperature structural materials with the potential to replace nickel-based high-temperature alloys in aerospace and marine engine hot-end components [1][2][3][4]. TiAl alloys also have higher specific stiffness, higher temperature-specific strength, and lower coefficients of expansion than both nickel-based high-temperature alloys and conventional titanium alloys, making them particularly suitable for making components with high dimensional stability requirements [5,6], such as aircraft engine cases. An aero-engine case usually consists of an outer ring, an inner ring, and support plates connecting the inner and outer rings, with some complex case components having a shunt ring between the inner and outer rings.…”
Section: Introductionmentioning
confidence: 99%